The Relationship Between Parity and the Incidence of Perineal Rupture: Literature Review - Junior, Herlambang Andreka; Fujiko, Masyita; Purnama, Rahmiaty (Journal of Midwifery and Nursing, 2025)
Perineal ruptureis an injury to the birth canal that occurs during the birth of a baby, either using or without tools. Perineal rupture is the second highest cause of postpartum maternal hemorrhage. Primiparous women are more likely to experience perineal rupture than multiparous women. The purpose of this literature review is to determine the relationship between parity and the incidence of perineal rupture in postpartum women. Using the literature review method with the PRISMA Flow Diagram principle. Articles or scientific journals were downloaded from PubMed, Portal Garuda, and Google Scholar with SINTA IV and V standards. The keywords in this article search were parity and perineal rupture. 197 articles were obtained in the search results. All articles were selected based on the inclusion criteria, 10 research articles were obtained to be reviewed. The results showed that there was a relationship between parity and the incidence of perineal rupture where the lower the parity, the higher the risk of perineal rupture.